2017
DOI: 10.1117/1.jbo.22.7.076006
|View full text |Cite
|
Sign up to set email alerts
|

Handheld optical coherence tomography–reflectance confocal microscopy probe for detection of basal cell carcinoma and delineation of margins

Abstract: We present a hand-held implementation and preliminary evaluation of a combined optical coherence tomography (OCT) and reflectance confocal microscopy (RCM) probe for detecting and delineating the margins of basal cell carcinomas (BCCs) in human skin Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 15 publications
1
54
0
Order By: Relevance
“…RCM-OCT imaging was performed using the hand-held probe, the technical details for which are previously described. 25 RCM imaging is with a lateral resolution of ~1 µm, optical sectioning of ~3 µm, with en face field of view (FOV) of 750×750 µm. OCT imaging is with lateral resolution of ~5 µm, axial resolution of 10 µm, and orthogonal FOV of 1000 µm deep × 2000 µm wide.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RCM-OCT imaging was performed using the hand-held probe, the technical details for which are previously described. 25 RCM imaging is with a lateral resolution of ~1 µm, optical sectioning of ~3 µm, with en face field of view (FOV) of 750×750 µm. OCT imaging is with lateral resolution of ~5 µm, axial resolution of 10 µm, and orthogonal FOV of 1000 µm deep × 2000 µm wide.…”
Section: Methodsmentioning
confidence: 99%
“…We placed adhesive paper rings (3M, Flemington, NJ) at the clinical margins for image navigation; this is a previously proven method. 25,26 Dermoscopic examination was subsequently carried out with a handheld dermatoscope within the paper ring. The ring divided the lesion in four hypothetical quadrants; the imaging in dermoscopically-suspicious areas was guided through these quadrants and clock positions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical coherence tomography (OCT) has been demonstrated for imaging the in vivo tumor resection bed in human subjects during breast cancer surgery, yielding a sensitivity and specificity of 91.7% and 92.1%, respectively, for detecting positive margins (Fig. 1), 52 as well as for imaging the surgical margins of resected tumor specimens 19,20,[53][54][55] and loco-regional lymph nodes in human breast cancer surgeries. 56 Related to OCT, optical coherence elastography provides 3-D maps of tissue mechanical properties, on the micrometer to millimeter scale.…”
Section: Other Label-free Optical Imaging Technologies For Assessing mentioning
confidence: 99%
“…Accurate identification of varying types of breast malignancies was demonstrated, and the study was enhanced by clinically relevant data analysis in which entire images were reviewed (rather than a selection of smaller ROIs) and compared to standard histology. Iftimia et al 19 demonstrated the possibility of combining OCT as a fast, low-resolution technique for screening for suspicious areas in large specimens with confocal microscopy, a slower but higher resolution technique for detailed analysis of suspicious areas. This is an attractive strategy that can seamlessly integrate the technical advantages of multiple techniques while minimizing the practical limitations of each.…”
Section: Breast Cancer Surgery: a Surgicalmentioning
confidence: 99%